Powder dipping process for plastic parts
Through the improved powder impregnation process and the use of surface treatment agents, the problem of low gloss on the surface of plastic parts is solved, achieving higher gloss and better resistance to ultraviolet rays and mechanical properties.
Patent Information
- Application Number
- CN202411567700.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
After the existing plastic parts are processed through the powder immersion process, the surface gloss is low, which affects the user experience.
A modified powder impregnation process is adopted to form a dense UV and anti-oxidation coating through sandblasting, ultrasonic oil removal, spraying and washing, spot welding, preheating, powder impregnation, curing, cooling and other steps, and surfactant, including brightening agents, surfactants, lignin/titanium dioxide composite materials and hexadecanol esters, forming a dense UV and anti-oxidation coating to improve the gloss and mechanical properties of plastic parts.
It significantly improves the surface gloss and retention time of plastic parts, enhancing its UV resistance and mechanical strength.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of plastic parts processing, and in particular to a powder dipping process for plastic parts. Background Art
[0002] Powder dipping is a commonly used coating processing technology, which is suitable for coating processing on the surfaces of various metals, plastics and other materials. Compared with traditional spraying technology, powder dipping has better adhesion, corrosion resistance and oxidation resistance, and is suitable for use in various environments and complex working conditions.
[0003] Usually, the coating is prepared using thermoplastic resin powder or thermosetting resin powder. Different powder materials are selected according to different substrates and working conditions. Before processing, the coating powder needs to be sieved to remove larger and smaller impurity particles to ensure uniformity and stability of the coating.
[0004] In the related art, the bowl baskets used in dishwashers are mostly made of PA material, PP material or stainless steel. For the bowl baskets made of PA material and PP material, the outer side of the bowl basket needs to be processed by a powder dipping process to form a coating. For example, the outer side of the PA material product is attached with PA material, and the outer side of the PP material is attached with PP material. The coating formed by the powder dipping process has a low surface gloss and a poor appearance, which affects the user experience when using the bowl basket.
[0005] Therefore, how to effectively improve the glossiness of plastic surface has become an urgent problem to be solved. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present application provides a powder dipping process for plastic parts.
[0007] In a first aspect, the present application provides a powder dipping process for plastic parts, which adopts the following technical solution: A powder dipping process for plastic parts, comprising the following steps: subjecting the plastic parts to sandblasting, ultrasonic degreasing, spraying water washing, spot welding, spraying water washing, preheating, powder dipping, curing, and cooling to obtain the powder-dipping plastic parts; The cooling steps are as follows: (1) dissolving a surface treatment agent in water to obtain a coolant; (2) placing the plastic part into a coolant for cooling to obtain a cooled plastic part; The surface treatment agent comprises the following raw materials in parts by weight: 15-25 parts of a brightener, 5-15 parts of a surfactant, 10-20 parts of a lignin / titanium dioxide composite material and 4-8 parts of hexadecyl alcohol ester.
[0008] Since plastic is exposed to oxygen or ultraviolet radiation in the air for a long time, an oxidation reaction will occur, causing the surface to become rough and black. By adopting the above-mentioned technical scheme, a lignin / titanium dioxide composite material is added in the present application. The added lignin / titanium dioxide composite material has a smaller particle size and good dispersibility, ultraviolet shielding performance, and antioxidant performance. The added lignin / titanium dioxide composite material is combined with the surface of the plastic part under the action of a surfactant and hexadecanol ester, and forms a dense anti-ultraviolet and anti-oxidation coating on the plastic surface, which plays a good protective role on the surface of the plastic part, so that the surface of the plastic part has good ultraviolet shielding performance and antioxidant performance.
[0009] In the present application, the formula is improved by adding hexadecanol ester, which has film-forming properties and slow volatilization rate. After each substance is dissolved in deionized water, an oily composite film is formed on the surface of the plastic part, which can keep the surface of the plastic part bright for a long time.
[0010] In the present application, the formula is improved by adding a brightener. Under the action of a surfactant and hexadecanol ester, the brightener is better in contact with the surface of the plastic part, thereby improving its adhesion and treatment effect; the added brightener forms a protective film on the surface of the plastic part, which can keep the surface of the plastic part bright for a long time.
[0011] In the present application, after the plastic parts are solidified, a surfactant is added to the water tank in which the product is immersed during the cooling stage. The surfactant activates the coating surface, so that the surface of the product becomes bright after being immersed in water and cooled. The surface of the product treated by this process can remain bright for a long time, and the addition of the surfactant helps prevent the product from shrinking in the cooling water to form voids.
[0012] By adopting the above technical scheme, the brightener, surfactant, lignin / titanium dioxide composite material and hexadecyl alcohol ester cooperate with each other, so that the plastic parts have higher gloss and good ultraviolet shielding performance, antioxidant performance and mechanical properties.
[0013] Preferably, the surface treatment agent further comprises 5-10 parts by weight of a grafted polyethylene / glyceryl monostearate grafted SiO2 blend.
[0014] By adopting the above technical scheme, the added grafted polyethylene / glyceryl monostearate grafted SiO2 blend, under the action of surfactant and hexadecanol ester, makes the grafted polyethylene / glyceryl monostearate grafted SiO2 blend better contact with the surface of plastic parts, effectively avoiding condensation on the surface of plastic parts due to excessive temperature difference during the processing of plastic parts, and effectively improving the mechanical properties of plastic parts.
[0015] Preferably, the brightener is at least one of acrylonitrile-styrene copolymer, styrene-butadiene block copolymer, butadiene-styrene copolymer, and maleic anhydride grafted polyolefin.
[0016] Preferably, the surfactant is at least one of anionic surfactant, nonionic surfactant and amphoteric surfactant.
[0017] In a specific embodiment, the surfactant can be replaced by a detergent containing a surfactant, and the addition of the detergent helps prevent the product from shrinking in cooling water to form voids, and reduces processing costs.
[0018] Preferably, the anionic surfactant is at least one of sodium fatty alcohol polyoxyethylene ether sulfate, sodium fatty alcohol polyoxyethylene ether carboxylate, sodium alkyl sulfonate, and sodium α-olefin sulfonate.
[0019] Preferably, the nonionic surfactant is at least one of fatty alcohol polyoxyethylene ether-9, fatty alcohol polyoxyethylene ether-7, polyethylene glycol, alkyl glucoside, oleic acid monoglyceride, sucrose ester, fatty acid methyl ester ethoxylate, polyglycerol fatty acid ester, and amine oxide.
[0020] Preferably, the amphoteric surfactant is at least one of lauryl alanine diethanolamine salt, sodium lauryl aminopropionate, and betaine.
[0021] Preferably, in step (2), the temperature of the coolant is 50°C-60°C; and the cooling time is 1s-7s.
[0022] Preferably, the mass ratio of the surface treatment agent to water in step (1) is (1-5):10.
[0023] Preferably, the preparation steps of the surface treatment agent are as follows: Weigh each raw material according to the recipe; The brightener, the surfactant, the lignin / titanium dioxide composite material, the grafted polyethylene / glyceryl monostearate grafted SiO2 blend, the hexadecyl alcohol ester and water are mixed to obtain a surface treatment agent.
[0024] Preferably, the mixing time is 20-35 minutes.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: The present application discloses a powder dipping process for plastic parts, which effectively improves the surface glossiness and retention time of the plastic parts by adding a surface treatment agent to the plastic parts during the cooling step, so that the prepared plastic parts have good UV resistance and mechanical strength. DETAILED DESCRIPTION
[0026] The technical solution of the present application is further illustrated by specific embodiments below. The specific embodiments do not limit the protection scope of the present application; some non-essential modifications and adjustments made by others based on the concept of the present application still fall within the protection scope of the present application.
[0027] The raw materials involved in this application are all commercially available products, among which: Acrylonitrile-styrene copolymer, molecular weight 157.21646; Fatty alcohol polyoxyethylene ether sodium sulfate, molecular weight 272.37987; Sodium lauryl aminopropionate, molecular weight 279.39397; Fatty alcohol polyoxyethylene ether-9, AEO-9, molecular weight 582.81; Hexadecyl alcohol ester, molecular weight is 286.407.
[0028] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0029] Source of raw materials: The preparation steps of lignin / titanium dioxide composite material are as follows: (1) After mixing 6 mL of carbon nanofiber (solid content 2%) and 1.5 g of lignin, 30 mL of anhydrous ethanol was added and mixed for 30 minutes, 10 mL of butyl titanate was added and mixed for 20 minutes, 2 mL of 20 wt% sulfuric acid solution was added and mixed, and then the mixture was put into a high-temperature and high-pressure reactor, sealed, and reacted at 120° C. for 2 hours. The reactor was cooled to 80° C., dried and aged to obtain a lignin / titanium dioxide composite material.
[0030] (2) Add 15 g of TOCNF gel (carboxylated nanocellulose, solid content 2%) to 15 mL of deionized water for dissolution, add lignin / titanium dioxide composite material (the amount added is 10% of the solid content of TOCNF gel) and mix for 30 minutes at a speed of 200 r / min; then move to an ultrasonic disperser and ultrasonically disperse for 10 minutes to obtain a lignin / titanium dioxide composite material.
[0031] Preparation of grafted polyethylene / glyceryl monostearate grafted SiO2 blends, the steps are as follows: (1) After mixing 100 mL of deionized water and 300 mL of anhydrous ethanol, add 4 g of nano-silicon dioxide and disperse by ultrasonication for 2 hours; (2) adding 10 mL of anhydrous ethanol and 10 mL of acetic acid solution to 0.8 g of KH570, mixing, and adding to the mixture prepared in step (1), reacting at 75° C. for 4 hours, centrifuging at 8000 r / min for 10 minutes, and drying at 80° C. for 12 hours to obtain modified nano-silica; (3) melting monostearate acrylate diglycerol at 80° C., adding azobisisobutyronitrile and modified nano-silica, introducing nitrogen gas for reaction for 8 hours to obtain a silica grafted product, wherein the mass ratio of modified nano-silica / monostearate acrylate diglycerol / azobisisobutyronitrile is 1:5:0.05; (4) Add 5 g of silica grafted material to a beaker, melt at 60°C, add 30 mL of acetone, stir for 10 min, and let stand in air and room temperature for 1 h; after solid-liquid separation, pour off the upper liquid, and add acetone again to repeat the experiment until the upper liquid becomes colorless and clear; remove the remaining acetone from the obtained precipitate using a rotary evaporator, and dry the solid after rotary evaporation at 60°C in vacuum for 3 h to obtain SiO2-g-PAGMS grafted material; (5) SiO2-g-PAGMS grafted product, linear low-density polyethylene (LLDPE), and bisphenol AF were mixed in a mass ratio of 145:340:10 to obtain a grafted polyethylene / glyceryl monostearate grafted SiO2 blend.
[0032] Preparation Example 1: The preparation steps of the surface treatment agent are as follows: (1) Weigh the following raw materials according to the formula: 20 kg of brightener, 10 kg of surfactant, 15 kg of lignin / titanium dioxide composite material, 6 kg of hexadecyl alcohol ester and 70 kg of water.
[0033] The brightener is a copolymer of acrylonitrile and styrene.
[0034] The surfactant is a mixture of sodium fatty alcohol polyoxyethylene ether sulfate, sodium lauryl aminopropionate and fatty alcohol polyoxyethylene ether-9, with a mass ratio of 3:1:1.
[0035] (2) The brightener, the surfactant, the lignin / titanium dioxide composite material, the hexadecanol ester and water were mixed for 30 minutes to obtain a surface treatment agent.
[0036] Preparation Example 2: The preparation steps of the surface treatment agent are as follows: (1) Weigh the following raw materials according to the formula: 15 kg of brightener, 5 kg of surfactant, 10 kg of lignin / titanium dioxide composite material, 4 kg of hexadecyl alcohol ester and 60 kg of water.
[0037] The brightener is a copolymer of acrylonitrile and styrene.
[0038] The surfactant is a mixture of sodium fatty alcohol polyoxyethylene ether sulfate, sodium lauryl aminopropionate and fatty alcohol polyoxyethylene ether-9, with a mass ratio of 3:1:1.
[0039] (2) The brightener, the surfactant, the lignin / titanium dioxide composite material, the hexadecyl alcohol ester and water were mixed for 30 minutes to obtain a surface treatment agent.
[0040] Preparation Example 3: The preparation steps of the surface treatment agent are as follows: (1) Weigh the following raw materials according to the formula: 25 kg of brightener, 15 kg of surfactant, 20 kg of lignin / titanium dioxide composite material, 8 kg of hexadecyl alcohol ester and 80 kg of water.
[0041] The brightener is a copolymer of acrylonitrile and styrene.
[0042] The surfactant is a mixture of sodium fatty alcohol polyoxyethylene ether sulfate, sodium lauryl aminopropionate and fatty alcohol polyoxyethylene ether-9, with a mass ratio of 3:1:1.
[0043] (2) The brightener, the surfactant, the lignin / titanium dioxide composite material, the hexadecyl alcohol ester and water were mixed for 30 minutes to obtain a surface treatment agent.
[0044] Preparation Example 4: The preparation steps of the surface treatment agent are as follows: (1) Weigh the following raw materials according to the formula: 20 kg of brightener, 10 kg of surfactant, 15 kg of lignin / titanium dioxide composite material, 6 kg of hexadecyl alcohol ester, 8 kg of grafted polyethylene / monostearin grafted SiO2 blend, and 70 kg of water.
[0045] The brightener is a copolymer of acrylonitrile and styrene.
[0046] The surfactant is a mixture of sodium fatty alcohol polyoxyethylene ether sulfate, sodium lauryl aminopropionate and fatty alcohol polyoxyethylene ether-9, with a mass ratio of 3:1:1.
[0047] (2) The brightener, the surfactant, the lignin / titanium dioxide composite material, the grafted polyethylene / glyceryl monostearate grafted SiO2 blend, the hexadecyl alcohol ester and water were mixed for 30 minutes to obtain a surface treatment agent.
[0048] Preparation Example 5: The preparation steps of the surface treatment agent are as follows: (1) Weigh the following raw materials according to the formula: 20 kg of brightener, 10 kg of surfactant, 15 kg of lignin / titanium dioxide composite material, 6 kg of hexadecyl alcohol ester, 5 kg of grafted polyethylene / monostearin grafted SiO2 blend, and 70 kg of water.
[0049] The brightener is a copolymer of acrylonitrile and styrene.
[0050] The surfactant is a mixture of sodium fatty alcohol polyoxyethylene ether sulfate, sodium lauryl aminopropionate and fatty alcohol polyoxyethylene ether-9, with a mass ratio of 3:1:1.
[0051] (2) The brightener, the surfactant, the lignin / titanium dioxide composite material, the grafted polyethylene / glyceryl monostearate grafted SiO2 blend, the hexadecyl alcohol ester and water were mixed for 30 minutes to obtain a surface treatment agent.
[0052] Preparation Example 6: The preparation steps of the surface treatment agent are as follows: (1) Weigh the following raw materials according to the formula: 20 kg of brightener, 10 kg of surfactant, 15 kg of lignin / titanium dioxide composite material, 6 kg of hexadecyl alcohol ester, 10 kg of grafted polyethylene / monostearin grafted SiO2 blend, and 70 kg of water.
[0053] The brightener is a copolymer of acrylonitrile and styrene.
[0054] The surfactant is a mixture of sodium fatty alcohol polyoxyethylene ether sulfate, sodium lauryl aminopropionate and fatty alcohol polyoxyethylene ether-9, with a mass ratio of 3:1:1.
[0055] (2) The brightener, the surfactant, the lignin / titanium dioxide composite material, the grafted polyethylene / glyceryl monostearate grafted SiO2 blend, the hexadecyl alcohol ester and water were mixed for 30 minutes to obtain a surface treatment agent.
[0056] Embodiment 1: A powder dipping process for plastic parts, comprising the following steps: subjecting the plastic parts to sandblasting, ultrasonic degreasing, spraying water washing, spot welding, spraying water washing, preheating, powder dipping, curing, and cooling to obtain the powder-dipping plastic parts; The details are as follows: (1) Hanging on plastic parts; (2) Sand blasting: processing time is 150 seconds, current is 7A; (3) Ultrasonic degreasing: Use a degreasing agent (commercially available) for ultrasonic degreasing, with a treatment time of 75 seconds and a treatment temperature of 38°C; (4) Spray washing: Use tap water for spray washing at room temperature for 80 seconds; (5) Spot welding: electric welding accessories, welding current is 10KVA; (6) Spray washing: Use tap water for spray washing at room temperature for 100 seconds; (7) Preheating: The preheating time is 165 seconds and the preheating temperature is 380°C; (8) Dipping powder: Dipping powder time is 3 seconds; powdering time is 5.2 seconds; (9) Curing: the curing temperature is 200°C and the curing time is 90 seconds; (10) Cooling: (a) dissolving 3 kg of the surface treatment agent in 10 kg of water to obtain a coolant; (b) adjusting the temperature of the coolant to 55° C., placing the plastic part in the coolant for cooling for 5 seconds, and obtaining a cooled plastic part; (11) Cut off the remaining hanging equipment.
[0057] The surface treatment agent was prepared in Preparation Example 1.
[0058] Embodiment 2: A powder dipping process for plastic parts, comprising the following steps: subjecting the plastic parts to sandblasting, ultrasonic degreasing, spraying water washing, spot welding, spraying water washing, preheating, powder dipping, curing, and cooling to obtain the powder-dipping plastic parts; The details are as follows: (1) Hanging on plastic parts; (2) Sand blasting: processing time is 150 seconds, current is 7A; (3) Ultrasonic degreasing: Use a degreasing agent (commercially available) for ultrasonic degreasing, with a treatment time of 75 seconds and a treatment temperature of 38°C; (4) Spray washing: Use tap water for spray washing at room temperature for 80 seconds; (5) Spot welding: electric welding accessories, welding current is 10KVA; (6) Spray washing: Use tap water for spray washing at room temperature for 100 seconds; (7) Preheating: The preheating time is 165 seconds and the preheating temperature is 380°C; (8) Dipping powder: Dipping powder time is 3 seconds; powdering time is 5.2 seconds; (9) Curing: the curing temperature is 200°C and the curing time is 90 seconds; (10) Cooling: (a) dissolving 1 kg of the surface treatment agent in 10 kg of water to obtain a coolant; (b) adjusting the temperature of the coolant to 50° C., placing the plastic part in the coolant for cooling for 5 seconds, and obtaining a cooled plastic part; (11) Cut off the remaining hanging equipment.
[0059] The surface treatment agent was prepared in Preparation Example 1.
[0060] Embodiment 3: A powder dipping process for plastic parts, comprising the following steps: subjecting the plastic parts to sandblasting, ultrasonic degreasing, spraying water washing, spot welding, spraying water washing, preheating, powder dipping, curing, and cooling to obtain the powder-dipping plastic parts; The details are as follows: (1) Hanging on plastic parts; (2) Sand blasting: processing time is 150 seconds, current is 7A; (3) Ultrasonic degreasing: Use a degreasing agent (commercially available) for ultrasonic degreasing, with a treatment time of 75 seconds and a treatment temperature of 38°C; (4) Spray washing: Use tap water for spray washing at room temperature for 80 seconds; (5) Spot welding: electric welding accessories, welding current is 10KVA; (6) Spray washing: Use tap water for spray washing at room temperature for 100 seconds; (7) Preheating: The preheating time is 165 seconds and the preheating temperature is 380°C; (8) Dipping powder: Dipping powder time is 3 seconds; powdering time is 5.2 seconds; (9) Curing: the curing temperature is 200°C and the curing time is 90 seconds; (10) Cooling: (a) dissolving 5 kg of a surface treatment agent in 10 kg of water to obtain a coolant; (b) adjusting the temperature of the coolant to 60° C., placing the plastic part in the coolant for cooling for 5 seconds, and obtaining a cooled plastic part; (11) Cut off the remaining hanging equipment.
[0061] The surface treatment agent was prepared in Preparation Example 1.
[0062] Embodiment 4: The difference from Example 1 is that the surface treatment agent is prepared in Preparation Example 2.
[0063] Embodiment 5: The difference from Example 1 is that the surface treatment agent is prepared in Preparation Example 3.
[0064] Embodiment 6: The difference from Example 1 is that the surface treatment agent is prepared in Preparation Example 4.
[0065] Embodiment 7: The difference from Example 1 is that the surface treatment agent is prepared in Preparation Example 5.
[0066] Embodiment 8: The difference from Example 1 is that the surface treatment agent is prepared in Preparation Example 6.
[0067] Comparative Example 1: The difference from Example 1 is that no surface treatment agent is added when cooling the plastic part.
[0068] Comparative Example 2: The difference from Example 6 is that no surface treatment agent is added when cooling the plastic parts.
[0069] Comparative Example 3: The difference from Example 1 is that when preparing the surface treatment agent, no lignin / titanium dioxide composite material is added.
[0070] Comparative Example 4: The difference from Example 6 is that when preparing the surface treatment agent, no lignin / titanium dioxide composite material is added.
[0071] Comparative Example 5: The difference from Example 1 is that no surfactant is added when preparing the surface treatment agent.
[0072] Comparative Example 6: The difference from Example 6 is that no surfactant is added when preparing the surface treatment agent.
[0073] Performance testing: 1. Glossiness detection: The glossiness and retention time of the plastic parts prepared in the examples and comparative examples were tested using a micro gloss meter A-4430 (BYK, Germany). The results are as follows: Table 1 Glossiness test results Glossiness (T / O) / % Keep time (days) Example 1 89 30 Example 2 85 25 Example 3 86 26 Example 4 87 27 Example 5 88 28 Example 6 95 38 Example 7 92 34 Example 8 93 36 Comparative Example 1 75 20 Comparative Example 2 82 25 Comparative Example 3 80 21 Comparative Example 4 86 29 Comparative Example 5 83 23 Comparative Example 6 90 31 It can be seen from Table 1 that the plastic parts prepared by the method of the present application have high gloss and can be maintained for up to 38 days.
[0074] Combined with the test results of Examples 1-8, it can be seen that the test results of Examples 6-8 are better than the test results of Examples 1-5, indicating that the addition of grafted polyethylene / glyceryl monostearate grafted SiO2 blend further improves the glossiness of the product and effectively prolongs the gloss retention time.
[0075] Combining Example 1 and Comparative Example 1, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 1, which shows that the addition of the surface treatment agent in the present application further improves the glossiness of the product and effectively prolongs the gloss retention time.
[0076] Combining Example 6 and Comparative Example 2, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 2, indicating that the addition of the surface treatment agent in the present application further improves the glossiness of the product and effectively prolongs the gloss retention time.
[0077] Combining Example 1 and Comparative Example 3, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 3, indicating that the addition of lignin / titanium dioxide composite material in the present application further improves the glossiness of the product and effectively prolongs the gloss retention time.
[0078] Combining Example 6 and Comparative Example 4, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 4, indicating that the addition of lignin / titanium dioxide composite material in the present application further improves the glossiness of the product and effectively prolongs the gloss retention time.
[0079] Combining Example 1 and Comparative Example 5, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 5, indicating that the addition of surfactant in the present application further improves the glossiness of the product and effectively prolongs the gloss retention time.
[0080] Combining Example 6 and Comparative Example 6, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 6, which shows that the addition of surfactant in the present application further improves the glossiness of the product and effectively prolongs the gloss retention time.
[0081] 2. Ultraviolet detection: Using the plastic ultraviolet light exposure test method ASTM D4329-05, the plastic parts prepared in the examples and comparative examples were placed under ultraviolet light for irradiation, and the aging degree of the plastic parts was observed at different time periods.
[0082] Table 2 Effect of UV irradiation on plastic aging (UV intensity 3000uW / cm 2 ) It can be seen from Table 2 that the degree of aging of the plastic parts prepared by the method of the present application is significantly reduced under ultraviolet irradiation.
[0083] Combined with the test results of Examples 1-8, it can be seen that the test results of Examples 6-8 are better than the test results of Examples 1-5, indicating that the addition of grafted polyethylene / glyceryl monostearate grafted SiO2 blend further improves the UV resistance of the product.
[0084] Combining Example 1 and Comparative Example 1, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 1, indicating that the addition of the surface treatment agent in the present application further improves the anti-ultraviolet performance of the product.
[0085] Combining Example 6 and Comparative Example 2, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 2, indicating that the addition of the surface treatment agent in the present application further improves the anti-ultraviolet performance of the product.
[0086] Combining Example 1 and Comparative Example 3, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 3, indicating that the addition of the lignin / titanium dioxide composite material in the present application further improves the anti-ultraviolet performance of the product.
[0087] Combining Example 6 and Comparative Example 4, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 4, indicating that the addition of the lignin / titanium dioxide composite material in the present application further improves the anti-ultraviolet performance of the product.
[0088] Combining Example 1 and Comparative Example 5, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 5, indicating that the addition of surfactant in the present application further improves the anti-ultraviolet performance of the product.
[0089] Combining Example 6 and Comparative Example 6, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 6, which shows that the addition of surfactant in the present application further improves the anti-ultraviolet performance of the product.
[0090] 3. Mechanical strength test: The tensile properties of the plastic parts prepared in the examples and comparative examples were tested, and the tensile strength and elongation at break of the plastic parts were tested with reference to GB / T1040.2-2006 standard.
[0091] Table 3 Tensile strength and elongation at break It can be seen from Table 3 that the plastic parts prepared by the method of the present application have good mechanical strength.
[0092] Combined with the test results of Examples 1-8, it can be seen that the test results of Examples 6-8 are better than the test results of Examples 1-5, indicating that the addition of grafted polyethylene / glyceryl monostearate grafted SiO2 blend further improves the tensile strength and elongation at break of the product, and effectively improves the mechanical properties of the product.
[0093] Combining Example 1 and Comparative Example 1, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 1, indicating that the addition of the surface treatment agent in the present application further improves the tensile strength and elongation at break of the product, and effectively improves the mechanical properties of the product.
[0094] Combining Example 6 and Comparative Example 2, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 2, indicating that the addition of the surface treatment agent in the present application further improves the tensile strength and elongation at break of the product, and effectively improves the mechanical properties of the product.
[0095] Combining Example 1 and Comparative Example 3, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 3, indicating that the addition of lignin / titanium dioxide composite material in the present application further improves the tensile strength and elongation at break of the product, and effectively improves the mechanical properties of the product.
[0096] Combining Example 6 and Comparative Example 4, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 4, indicating that the addition of lignin / titanium dioxide composite material in the present application further improves the tensile strength and elongation at break of the product, and effectively improves the mechanical properties of the product.
[0097] Combining Example 1 and Comparative Example 5, it can be seen that the test result of Example 1 is better than the test result of Comparative Example 5, indicating that the addition of surfactant in the present application further improves the tensile strength and elongation at break of the product, and effectively improves the mechanical properties of the product.
[0098] Combining Example 6 and Comparative Example 6, it can be seen that the test result of Example 6 is better than the test result of Comparative Example 6, indicating that the addition of surfactant in the present application further improves the tensile strength and elongation at break of the product, and effectively improves the mechanical properties of the product.
Claims
1. A powder dipping process for plastic parts, characterized in that: The steps are as follows: the plastic parts are subjected to sandblasting, ultrasonic degreasing, spray water washing, spot welding, spray water washing, preheating, powder dipping, curing, and cooling to obtain the powder-dipping plastic parts; The cooling steps are as follows: (1) Dissolving the surface treatment agent in water to obtain a coolant; (2) placing the plastic part into a coolant for cooling to obtain a cooled plastic part; The surface treatment agent comprises the following raw materials in parts by weight: 15-25 parts of a brightener, 5-15 parts of a surfactant, 10-20 parts of a lignin / titanium dioxide composite material and 4-8 parts of hexadecyl alcohol ester.
2. The powder dipping process for plastic parts according to claim 1, characterized in that: The surface treatment agent also includes 5-10 parts by weight of a grafted polyethylene / glyceryl monostearate grafted SiO2 blend.
3. The powder dipping process for plastic parts according to claim 1, characterized in that: The brightener is at least one of acrylonitrile-styrene copolymer, styrene-butadiene block copolymer, butadiene-styrene copolymer and maleic anhydride grafted polyolefin.
4. The powder dipping process for plastic parts according to claim 3, characterized in that: The surfactant is at least one of anionic surfactant, nonionic surfactant and amphoteric surfactant.
5. The powder dipping process for plastic parts according to claim 4, characterized in that: The anionic surfactant is at least one of sodium fatty alcohol polyoxyethylene ether sulfate, sodium fatty alcohol polyoxyethylene ether carboxylate, sodium alkyl sulfonate, and sodium α-olefin sulfonate; The nonionic surfactant is at least one of fatty alcohol polyoxyethylene ether-9, fatty alcohol polyoxyethylene ether-7, polyethylene glycol, alkyl glucoside, oleic acid monoglyceride, sucrose ester, fatty acid methyl ester ethoxylate, polyglycerol fatty acid ester, and amine oxide; The amphoteric surfactant is at least one of lauryl alanine diethanolamine salt, sodium lauryl aminopropionate and betaine.
6. The powder dipping process for plastic parts according to claim 1, characterized in that: The temperature of the coolant in step (2) is 50°C-60°C.
7. The powder dipping process for plastic parts according to claim 1, characterized in that: The cooling time in step (2) is 1s-7s.
8. The powder dipping process for plastic parts according to claim 1, characterized in that: The mass ratio of the surface treatment agent to water in the step (1) is (1-5):
10.
9. A powder dipping process for plastic parts according to claim 1, characterized in that: The preparation steps of the surface treatment agent are as follows: Weigh each raw material according to the recipe; The brightener, the surfactant, the lignin / titanium dioxide composite material, the grafted polyethylene / glyceryl monostearate grafted SiO2 blend and the hexadecyl alcohol ester are mixed to obtain a surface treatment agent.
10. The powder dipping process for plastic parts according to claim 9, characterized in that: The mixing time is 20-35 minutes.
Citation Information
Patent Citations
Long-acting brightening agent and preparation method thereof
CN107858688A
Polypropylene material modification technology for automobile bumper
CN109627572A
Primer-free thermosetting powder coating material and coating method thereof
CN118080288A